(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There has been a recent uptick in the number of violent crimes committed against women inIndia. Any sort of violence against women is a blatant violation of the basic rights of women, which areestablished in Articles 14 and 15 of the Constitution of India. This is the case regardless of the type ofabuse. Women in India’s patriarchal society continue to be oppressed and to be victims of a variety offorms of abuse, both inside and outside of their homes, despite the fact that there are a variety ofprovisions available to maintain the rights, dignity, and well-being of women. Despite these provisions,women in India’s patriarchal society continue to be oppressed. A recent report that was presented bythe National Crime Records Bureau (NCRB) stated that the number of crimes committed against womenin India increased from 3, 793 per million in 2016 to 3, 886 per million in 2017. However, the majority ofthe data is believed to be unreliable due to the fact that many cases do not get reported in India due tothe influence of factors such as social stigma, loss of family reputation, etc. As a result, the issue ofviolence against women and crimes committed against women is currently being discussed at thenational level in this country.